Diseño de un sistema de costos para la producción de verduras en la escuela de ciencias agrícolas y ambientales, PUCESI - Villarreal Gómez, Nicole Stefanía (2021)
This work reflects the results that have been obtained on the research, analysis and study regarding the design of a cost system for the production of vegetables from the School of Agricultural and Environmental Sciences (ECAA) of the Pontifical Catholic University of Ecuador Ibarra Headquarters (PUCE-SI) where the farm is located, which is a learning place for agricultural and livestock issues. Data have been obtained on the cost elements that are incurred in vegetable production\; research tools were used, such as the interview that was applied to the head of the farm. The lack of a costing system for the production of vegetables can be evidenced, so that the sale price is set by the central plant but not by the costing process, in this way it is necessary to design a cost system for the production where you get a real sale price.